2022
DOI: 10.1139/facets-2022-0140
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and discharge pathways of microplastics into freshwater ecosystems: A systematic review and meta-analysis

Abstract: Although many studies have focused on the importance of littering and (or) illegal dumping as a source of plastic pollution to freshwater, other relevant pathways should be considered, including wastewater, stormwater runoff, industrial effluent/runoff, and agricultural runoff. Here, we conducted a meta-analysis focused on these four pathways. We quantified the number of studies, amount and characteristics of microplastics reported, and the methods used to sample and measure microplastics from each pathway. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…However, nets will allow small and filamentous particles (i.e., fibers) to escape and show lower concentrations than samples collected without a net. In contrast, "grab" samples of some lower volume of water allow for all particles to be measured; however, the lower volume may lead to higher variation in concentrations among replicate samples (Wang et al, 2022). Our study was based on grab samples collected via an autosampler.…”
Section: Results From This Study Compared With Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, nets will allow small and filamentous particles (i.e., fibers) to escape and show lower concentrations than samples collected without a net. In contrast, "grab" samples of some lower volume of water allow for all particles to be measured; however, the lower volume may lead to higher variation in concentrations among replicate samples (Wang et al, 2022). Our study was based on grab samples collected via an autosampler.…”
Section: Results From This Study Compared With Literaturementioning
confidence: 99%
“…One consideration for interpretation of the data in this study is the role of sampling methodology and volume. Previous work suggests a trade‐off between high and low volume sampling in aquatic habitats (Barrows et al, 2017; Wang et al, 2022). High volume samples can be obtained via the passage of water through a net or sieve.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that several factors, such as precipitation, catchment size, type of land use, and analysis methodology (e.g., sampling volume and size of collected MPs), can influence the reported MP abundance in stormwater. , Järlskog et al . reported only 3 MPs/L of ≥100 μm in stormwater samples; however, this increased to 5900 MPs/L when analyzing smaller MPs (>20 μm).…”
Section: Resultsmentioning
confidence: 99%
“…), with leachates from tires more toxic to bacteria and microalgae compared to other polymers (polyethylene, poly(ethylene terephthalate), and polypropylene). 19 In a recent review study, Wang et al 20 showed a much higher abundance of MPs (mean 676 MPs/L from 25 studies) in stormwater runoff compared to other important land-based MP sources such as wastewater effluent (mean 12 MPs/L from 76 studies). This highlights the need to better understand the abundance of MPs in stormwater and to control this potentially important source of land-based MPs.…”
Section: Introductionmentioning
confidence: 99%
“…Municipal wastewater treatment plants (WWTPs) are key point sources of microplastics to freshwater environments (Sun et al, 2019; Wang et al, 2022). Though not specifically designed to remove them, wastewater treatment processes can reduce microplastics by upward of 99% (Gies et al, 2018); but their effectiveness depends on the type of treatment used (Gies et al, 2018; Iyare et al, 2020; Lares et al, 2018; Sun et al, 2019; Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%